Parametric Pedagogy: Integrating parametric CAD in Irish post-primary schools - McGarr, Oliver; Seery, Niall (Design and Technology Education: An International Journal, 2011)
Technology education in Irish post-primary schools is undergoing significant change. In recent years the syllabi of all technology-related subjects have been revised. A new subject, Design and Communication Graphics, has replaced the traditional Technical Drawing subject. This new subject aims to develop students’ spatial awareness and graphical communication skills in the context of design. Parametric CAD forms a significant element of the subject. This research paper reports on a study into the use of parametric CAD by teachers in Irish post-primary schools. The research found that teachers were enthusiastic and welcomed the inclusion of the software as part of their teaching. However, the novel teaching environment was challenging which had a significant affect on their pedagogical approaches. The findings highlight the need for affective teacher professional development that explores the declarative as well as the procedural knowledge required for mastery of the CAD software.